Pengaruh Pembiayaan Mikro Syariah Terhadap Tingkat Perkembangan Usaha Mikro Kecil Menengah (UMKM) - Muhammad Andi Prayogi; Lukman Hakim Siregar (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2017)
This research aims to see that the influence of micro financing sharia on the level of SMEs business development at PT. BRI Sharia Branch Medan. The research of this study to see that there is a significant effect of micro sharia financing on the Level of SMEs Business Development due to the value of t arithmetic> t table that is equal to 7.196 > 2.024 and t arithmetic is the rejection zone H0 so H0 rejected (Ha accepted). R-Square value of 0,577 or 57,70%, this means that variable of Business Development Level of UMKM (Y) influenced by variable of micro financing of sharia (X). The remaining 42.30% of the contribution of other variables are not belong in this research. based on the output of F test, F value count > F table is 51,775 > 3,24 with H0 hypothesis rejected and Ha accepted with significance 0,000 < 0,05 hence can be concluded that variable of Micro Financing of Syariah have significant influence to development level of UMKM business at PT. BRI Sharia Branch Medan